Psychophysiological Correlates of Emotional- and Alcohol-Related Cues Processing in Offspring of Alcohol-Dependent Patients. - Dominguez-Centeno, I; Jurado-Barba, R; Sion, A; Martínez-Maldonado, A; Castillo-Parra, G; López-Muñoz, F; Rubio, G; Martínez-Gras, I (Alcohol & Alcoholism, 2020)
Aims To determinate if offspring of alcohol-dependent patients (OA) process affective stimuli and alcohol-related cues in a different manner than control subjects do. Methods Event-related potentials (early posterior negativity [EPN]/ late positive potential [LPP]) and event-related oscillations (Theta) were obtained by electroencephalographic (EEG) recording during the viewing of International Affective Picture System (IAPS) images with positive, negative and neutral valence, as well as alcohol-related cues. The total sample was comprised of 60 participants, divided into two groups: one group consisted of OA (30) and the control group of participants with negative family history of alcohol use disorders (30). Results Theta power analysis implies a significant interaction between condition, region and group factors. Post-hoc analysis indicates an increased theta power for the OA at different regions, during pleasant (frontal, central, parietal, occipital, right temporal); unpleasant (frontal, central, occipital); alcohol (frontal, central, parietal, occipital, right and left temporal) and neutral (occipital) cues. There are no group differences regarding any of the event-related potential measurements (EPN/LPP). Conclusions There is evidence of alterations in the processing of affective stimuli and alcohol-related information, evidenced by changes in theta brain oscillations. These alterations are characterized by an increased emotional reactivity, evidenced by increased theta at posterior sites. There is also an increased recruitment of emotion control, which could be a compensation mechanism, evidenced by increased theta power at anterior sites during affective stimuli and alcohol cues.